Efficient and stable subzero operation of a PEM fuel cell with a composite anode using hydrogen-methanol composition during freeze/thaw cycles. (8th April 2023) - Ivanova, Nataliya A.; Spasov, Dmitry D.; Mensharapov, Ruslan M.; Kukueva, Elena V.; Zasypkina, Adelina A.; Fateev, Vladimir N.; Grigoriev, Sergey A.
Abstract: The present research deals with the adaptation of hydrogen-air fuel cells with proton exchange membrane (PEMFC) to autonomous periodic operation at subzero ambient temperatures. The main goal of the research is to limit the influence of subzero temperatures on component integrity and electrochemical performance stability of PEMFC in the cause of the freeze-thaw (F/T) cycling test. The MEAs stability in cycling from subzero (−35 °C) to operating temperature (+35 °C) was ensured without any specific preparatory operations modeling the PEMFC stop and "cold start" procedure. This is provided through the use of hydrogen-methanol compositions (no more than 4 vol % of methanol vapor) as fuel and a composite anode. Advanced membrane-electrode assembly (MEA) based on the composite anode layer (Pt 40 /C + Pt 20 /10 wt%–SnO2 /C) for efficient and stable subzero operation during F/T cycling. High stability of electrochemical performance of the MEA with the composite anode at subzero ambient temperatures is shown. Advantages of use a two-component fuel PEMFC for autonomous periodic operation at subzero ambient temperatures are highlighted. Graphical abstract: Image 1 Highlights: The hydrogen-methanol composition is applied as a fuel for cold start procedure. Efficiency of two-component anode in methanol vapor oxidation has been proven. Stability of fuel cell electrochemical performance at subzero temperatures is ensured.